Posible subvaloración del estado de la leptospirosis canina en Camagüey - Barreto Argilagos, Guillermo; Rodríguez Torrens, Herlinda de la C.; García Casas, Tatiana; Montes de Oca, Roberto Vázquez (apm, 2025)
Nota Técnica